Detection and Characterization of Circulating Tumor Cells in Patients with Merkel Cell Carcinoma - Riethdorf, Sabine; Hildebrandt, Lina; Heinzerling, Lucie; Heitzer, Ellen; Fischer, Nicole; Bergmann, Sonja; Mauermann, Oliver; Waldispuehl-Geigl, Julie; Coith, Cornelia; Schoen, Gerhard; Peine, Sven; Schuler, Gerold; et al. (Clinical Chemistry, 2019)
BACKGROUND: Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer with increasing incidence and high mortality rates. MCC has recently become the subject of immune checkpoint therapy, but reliable biomarkers for estimating prognosis, risk stratification, and prediction of response are missing.
CRIS-Team WoS Importer:2019-03-15